Effects of stimulus amplitude-scaling approach on emotional responses to non-speech sounds - Erin M. Picou; Shae D. Morgan; Elizabeth D. Young; Samantha J. Gustafson (PLoS ONE, 2025)
In the study of auditory emotion perception, it is important to calibrate test sounds so their presentation level during testing is known. It is also often desirable to standardize the amplitude of the sounds so that each sound used in testing is approximately the same level. However, existing literature in the study of auditory emotion perception includes a mixture of techniques for standardizing amplitude across sounds. The purpose of this study was to compare the effects of two amplitude-scaling approaches on emotional responses to non-speech sounds, specifically standardization based on peak level or root-mean-square (rms) level. Nineteen young adults provided ratings of valence and arousal via an online testing program. Stimuli were non-speech sounds scaled in two ways, based on the stimulus’ peak level or rms level. Ratings were analyzed using linear-mixed effects modeling to compare scaling methods; correlations between ratings and level within each scaling method were explored. Analysis revealed that the ratings of peak-scaled sounds were less pleasant and more exciting than were the ratings of rms-scaled sounds, although the effects were small in magnitude (~0.2 points on a 1–9 scale). Within rms-scaled sounds, peak level was not related to ratings of valence or arousal. However, within peak-scaled sounds, rms level was related to ratings of valence and arousal. Combined, these data suggest that amplitude standardization has a small effect on ratings overall, but investigators might be motivated to choose one approach over the other, depending on the research question. Rms-scaling reduces overall level as a cue for emotional responses, while peak-scaling maintains some natural variability in responses related to level. Finally, results are specific to this stimulus set. The effects of amplitude-scaling would be expected to be negligible for a stimulus set where the sounds have homogenous temporal dynamics.